2004
DOI: 10.1021/bi049812o
|View full text |Cite
|
Sign up to set email alerts
|

Xylose Isomerase in Substrate and Inhibitor Michaelis States:  Atomic Resolution Studies of a Metal-Mediated Hydride Shift,

Abstract: Xylose isomerase (E.C. 5.3.1.5) catalyzes the interconversion of aldose and ketose sugars and has an absolute requirement for two divalent cations at its active site to drive the hydride transfer rates of sugar isomerization. Evidence suggests some degree of metal movement at the second metal site, although how this movement may affect catalysis is unknown. The 0.95 A resolution structure of the xylitol-inhibited enzyme presented here suggests three alternative positions for the second metal ion, only one of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 35 publications
6
103
1
1
Order By: Relevance
“…These features of the reaction were similar to those of xylose isomerase, which adopts the hydride transfer mechanism. 18,24) These results suggest that B. subtilis MTR-1-P isomerase follows the hydride transfer mechanism in its isomerization reaction. An interesting point, unique to B. subtilis MTR-1-P isomerase, is that this enzyme catalyzed the reaction without the participation of a metal ion in the reaction (Table 1).…”
Section: )mentioning
confidence: 84%
See 1 more Smart Citation
“…These features of the reaction were similar to those of xylose isomerase, which adopts the hydride transfer mechanism. 18,24) These results suggest that B. subtilis MTR-1-P isomerase follows the hydride transfer mechanism in its isomerization reaction. An interesting point, unique to B. subtilis MTR-1-P isomerase, is that this enzyme catalyzed the reaction without the participation of a metal ion in the reaction (Table 1).…”
Section: )mentioning
confidence: 84%
“…19,20) The other mechanism is the hydride transfer mechanism, in which a hydride on a carbon is directly transferred to the neighboring cationic carbon. 18,23,24) In the isomerase reaction of B. subtilis MTR-1-P isomerase, the product of the enzyme reaction in the presence of 99.9% D 2 O showed no increase in mass after the reaction, in contrast to the case with R5P isomerase (Table 2), and was virtually deuterium-free in NMR analysis (Fig. 4, inset).…”
Section: )mentioning
confidence: 98%
“…The enzymatic isomerization step is believed to occur primarily at M2. First, a hydroxyl ion bound to M2 promotes deprotonation at O2 (17). Next, M2 forms a bidentate complex with both O1 and O2, withdrawing electron density from the C-O bonds and effectively polarizing the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…[21] In all three cases, the active metal center (Lewis acid) coordinates to oxygen atoms in the first shell and has a covalently bonded À OH (Brønsted base) group. In addition, it has been shown that the glucose molecule binds to [Cr(H 2 O) 5 …”
Section: Mechanism Of the Glucose-to-fructose Isomerizationmentioning
confidence: 99%
“…Thus, the isomerization catalyst should be compatible with the subsequent dehydration reaction, which is performed by using a Brønsted-acid catalyst at relatively high temperatures (> 413 K). The aldose-to-ketose isomerization is used in large industrial applications, which use enzymatic or base-catalyzed reactions; [5] however, neither of these processes is compatible with the dehydration reaction when using a single reactor. Thus, the development of catalysts for this reaction in aqueous media is an important milestone in our ability to utilize biomass.…”
Section: Introductionmentioning
confidence: 99%